Effects of Mesenchymal Stem Cell Treatment on Systemic Cytokine Levels in a Phase 1 Dose Escalation Safety Trial of Septic Shock Patients* - Schlosser, Kenny (Crit Care Med, 2019)
OBJECTIVES: Cellular Immunotherapy for Septic Shock is the first-in-human clinical trial evaluating allogeneic mesenchymal stem/stromal cells in septic shock patients. Here, we sought to determine whether plasma cytokine profiles may provide further information into the safety and biological effects of mesenchymal stem/stromal cell treatment, as no previous study has conducted a comprehensive analysis of circulating cytokine levels in critically ill patients treated with mesenchymal stem/stromal cells. DESIGN: Phase 1 dose-escalation trial. PATIENTS: The interventional cohort (n = 9) of septic shock patients received a single dose of 0.3, 1.0, or 3.0 million mesenchymal stem/stromal cells/kg body weight (n = 3 per dose). The observational cohort received no mesenchymal stem/stromal cells (n = 21). INTERVENTIONS: Allogeneic bone marrow-derived mesenchymal stem/stromal cells. MEASUREMENTS AND MAIN RESULTS: Serial plasma samples were collected at study baseline prior to mesenchymal stem/stromal cell infusion (0 hr), 1 hour, 4 hours, 12 hours, 24 hours, and 72 hours after mesenchymal stem/stromal cell infusion/trial enrollment. Forty-nine analytes comprised mostly of cytokines along with several biomarkers were measured. We detected no significant elevations in a broad range of pro-inflammatory cytokines and biomarkers between the interventional and observational cohorts. Stratification of the interventional cohort by mesenchymal stem/stromal cell dose further revealed patient-specific and dose-dependent perturbations in cytokines, including an early but transient dampening of pro-inflammatory cytokines (e.g., interleukin-1β, interleukin-2, interleukin-6, interleukin-8, and monocyte chemoattractant protein 1), suggesting that mesenchymal stem/stromal cell treatment may alter innate immune responses and underlying sepsis biology. CONCLUSIONS: A single infusion of up to 3 million cells/kg of allogeneic mesenchymal stem/stromal cells did not exacerbate elevated cytokine levels in plasma of septic shock patients, consistent with a safe response. These data also offer insight into potential biological mechanisms of mesenchymal stem/stromal cell treatment and support further investigation in larger randomized controlled trials.